Longitudinal Analysis (1994-2020) of Prevalence and Trends of Underweight in Polish Children - Aleksandra Lemanowicz-Kustra; Anna Borkowska; Michał Brzeziński; Adam Wyszomirski; Agnieszka Szlagatys-Sidorkiewicz (MDPI AG, 2021)
Nutritional status disorders are a worldwide problem. Approximately 5.9 million children under the age of five die each year, and 45% of these deaths are related to malnutrition. The aim of the study was to analyse the prevalence of underweight children aged between 6 and 7 years old, living in the Gdańsk, Poland, in the years 1994-2020. The anthropometric parameters of 67,842 children were analysed. BMI (Body Mass Index) value <5 percentile (pc) was defined as underweight. The BMI value was compared to the WHO (World Health Organization) centile charts and the OLAF (research project PL0080) national reference charts. The prevalence of underweight children in relation to the WHO charts was 1.9%; underweight status was found to be more significant in the group of boys (2.1%) than the group of girls (1.7%) (p < 0.001). According to the OLAF centile charts, the underweight figure among all of the study population was 2.1% and no statistical significance between boys (2.1%) and girls (2.0%) was found (p = 0.670). The occurrence of underweight indviduals in the studied group slightly increased in the years 1994-2020. We found a statistically significant increasing linear trend in the analysis of underweight children in our group (p < 0.001), in group of boys (p < 0.001), but not girls (WHO p = 0.603; OLAF p = 0.787). This points to the need to conduct regular screening systems for children and adolescents.